A Calcium Guard in the Outer Membrane: Is VDAC a Regulated Gatekeeper of Mitochondrial Calcium Uptake? - Sander, Paulina (Int J Mol Sci, 2021)
Already in the early 1960s, researchers noted the potential of mitochondria to take up large amounts of Ca(2+). However, the physiological role and the molecular identity of the mitochondrial Ca(2+) uptake mechanisms remained elusive for a long time. The identification of the individual components of the mitochondrial calcium uniporter complex (MCUC) in the inner mitochondrial membrane in 2011 started a new era of research on mitochondrial Ca(2+) uptake. Today, many studies investigate mitochondrial Ca(2+) uptake with a strong focus on function, regulation, and localization of the MCUC. However, on its way into mitochondria Ca(2+) has to pass two membranes, and the first barrier before even reaching the MCUC is the outer mitochondrial membrane (OMM). The common opinion is that the OMM is freely permeable to Ca(2+). This idea is supported by the presence of a high density of voltage-dependent anion channels (VDACs) in the OMM, forming large Ca(2+) permeable pores. However, several reports challenge this idea and describe VDAC as a regulated Ca(2+) channel. In line with this idea is the notion that its Ca(2+) selectivity depends on the open state of the channel, and its gating behavior can be modified by interaction with partner proteins, metabolites, or small synthetic molecules. Furthermore, mitochondrial Ca(2+) uptake is controlled by the localization of VDAC through scaffolding proteins, which anchor VDAC to ER/SR calcium release channels. This review will discuss the possibility that VDAC serves as a physiological regulator of mitochondrial Ca(2+) uptake in the OMM.